Workflow for wedding photographers the complete guide to processing and delivering your wedding photos in 2 days or less - Plicanic, Khara; Safari eBooks ([San Francisco, Calif.?] : Peachpit Press/AdobePress, 2014)
"Critically-acclaimed video training will help you shoot weddings like a pro. An experienced instructor presents up to 4 hours of high-quality HD video, complete with lesson files, assessment quizzes, and review materials. The video is wrapped in a unique interface that allows the viewer to jump to any topic and also bookmark individual sections for later review. Project files used in the lessons are included so viewers can practice what they've learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page.
Title from title screen.
Date of publication from resource description page (viewed June 3, 2014).
Presenter, Khara Plicanic.
Keywords: Wedding photography -- Processing; Wedding photography; Electronic books